Medicine reminder with low battery alert "MEDMINDER" / Syahirah Asyiqin Alias ... [et al.] - Alias, Syahirah Asyiqin; Fazilah Shuhaimi, Luqman Hakim; Kharul Anuar, Khairin Farhana; Mangsor, Muhammad Firdaus; Sulaıman, Suhana (2021)
Elderly who suffer with dementia tend to forget their daily routine in the new norm when living alone during lockdown. Furthermore, they require proper management for their medications. Taking wrong medicines at the wrong time including incorrect prescription, missed doses, or excessive dosage of medicine can lead to serious disease, hospital visits and even death. Even though a traditional medicine box is capable of resolving the management issue for prescription, there are several features that can be designed to assist the elderly in managing their daily prescription intakes. The current automated pill box is typically inexpensive and produces reliable performance. In addition, it allows users to administer on-time via increased accessibility in elderly care. However, their reminder box is sold for a normal 16×2 LCD panel. The size is too small for the elderly to see it clearly from a certain viewing distance especially for those who are facing vision loss. Medicine Reminder with Low Battery Alert (MEDMINDER) is designed as a portable medicine reminder box with a low battery alert function and to improvise the existing medicine box with additional features. In this work, the design uses Arduino Uno as controller and interface with the push button as input in performing action to set the alarm for the reminder. The output of the 20 × 4 LCD will display the time, date, and day of the alarm set together with the percentage of battery indicator. The LED was used to alert the elderly on the day that they should take their medicine by blinking along with the buzzer. Finally, the speaker will be added as an additional feature for elderly with dementia who are facing vision loss to hear the alert of time taken to eat their medicine and alert to do battery replacement once the battery is running out. MEDMINDER was tested using Proteus to emulate the concept of the pill compartment for the elderly.